Development of porous ceramic membrane from Industrial Sanitaryware Solid Waste / Norliza Ibrahim - Ibrahim, Norliza (Institute of Graduate Studies, UiTM, 2012)
Fabrication of ceramic membrane has been related to commercially available material which can be considered as high cost and its reduction was thus of great importance. Silica and alumina were the main ingredients that had been utilized in the fabrication of ceramic membrane. In this study, industrial waste from sanitaryware company had been selected as the raw material for ceramic membrane fabrication since it shown the presence of silica. The first objective of this research was to study the effect of particle size distributions (PSD), sintering temperature and binder concentration on the fabrication of ceramic membrane. It was then followed by characterization of the fabricated membrane. Next, the fabricated membrane was applied in cell separation process, and finally curve fitting and fouling model was analyzed. Extrusion process has been selected as the fabrication method.